Addressing healthcare professionals’ fatigue for effective climate action engagement - Eddie Robinson; Dinesh Bhandari; Ross Donohue; Zerina Lokmic-Tomkins (The Journal of Climate Change and Health)
Climate change is a significant threat to public health, exacerbating existing challenges in healthcare systems. The anticipated impacts encompassing increased global surface temperatures, rising sea levels, water and food insecurity, geopolitical instability and the heightened frequency, duration, and intensity of natural disasters coupled with the healthcare sector's contribution to carbon emissions, necessitate urgent action from healthcare professionals. However, while healthcare professionals are called to engage in climate action, defined as an action to combat climate change and its impacts, the healthcare workforce also faces unprecedented challenges exacerbated by the public health emergencies (e.g.: COVID-19 pandemic) such as fatigue, burnout, and workforce shortages. Dealing with these challenges leaves little opportunity or time for healthcare professionals to engage in climate change mitigation and adaptation. In this perspective paper, we outline the fundamental aspects of change fatigue and suggest solutions to engage healthcare professionals in climate action.